Design of radiation shields for infrared heaters. - Nieto Miranda, J. Jesús; Sánchez Aguilar, Jons; Castañeda Infante, Héctor; Carbajal Romero, Manuel Faraón (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
We present a numerical-experimental study of an infrared gas heater for the final drying of the superficial layer of paint impregnated in the leather. Radiation shields are designed and implemented to reflect heat to the leather in order to optimize its operation and minimize leakage or losses of heat. The design of the shields is made by means of numerical simulations using the finite element method and computer software. The efficiency of these shields by thermography studies was validated. The main objective of this work is to improve the industrial efficiency of the prototype employed.